Pathophysiological mechanisms and clinical consequences of exposure to new psychoactive substances ("salts") on a newborn - Elena V. Loshkova; Ivan V. Doroshenko; Tatiana S. Liulka; Anatoly I. Khavkin; Elena I. Kondratieva; Nuriniso D. Odinaeva; Yulia S. Rafikova; Viktor A. Zhelev; Andrey L. Solnyshko; Evgeniy V. Mikhalev; Sergey P. Ermolenko; Ivan R. Grishkevich; et al. (Union of pediatricians of Russia, 2023)
Background. The usage of new psychoactive substances (NPAS) is increasing every year among various social groups around the world. According to various authors, the use of abused drugs during pregnancy remains at a high level - from 2.8 to 7% of pregnant women. The usage of NPAS, as well as other groups of abused drugs, during pregnancy is fraught with intrauterine multi-organ damage, however, any organ and tissue specificity for NPAS has not been described. In intervention trials conducted on laboratory animals, negative pathophysiological mechanisms triggered by synthetic cathinones have been demonstrated in the form of increased proapoptotic activity, the formation of autophagolysosomes and reactive oxygen intermediates in cells of nervous tissue, and the pro-inflammatory orientation of cells of the immune system.Case report describes a predominant lesion of the nervous system (developmental brain malformations, damage to the inspiratory center) and the musculoskeletal system (pronounced miotonical syndrome, congenital pathological fractures of the femurs), leading to multiorgan dysfunction, uncontrolled inflammatory response and, as a result, to the development of severe disablement of such children and an increase in the cohort of palliative pediatric patients. In the article, the authors focus on the pathophysiological mechanisms of NPAS for a deeper and more holistic understanding of the pathological process occurring in the body, in order to form and improve the medical judgment of specialist doctors and cite their own clinical observation as an illustration of the consequences of using NPAS during pregnancy. The authors believe that this review describing the case report is valuable from the point of view of practical applicability both for clinicians of various fields and for researchers.Conclusion. In addition, it is necessary to pay attention to the fact that the use of NPAS is of great social and economic significance, the description of such clinical observations, as well as in vitro studies, is relevant, and the expansion of ideas about the short-term and long-term negative consequences of the use of NPAS should serve as an initiating stage for the development of rehabilitation strategies for these patients